NABI SEBAGAI MANUSIA POLITIS DALAM KENABIAN YESAYA DAN YEREMIA - Purnomo, Albertus (Jurnal Orientasi Baru, 2017)
Focus of this research is to examine main political characters of major prophets based on the book of Isaiah and Jeremiah. It explores aÂ method of exegetic analysis. The main result of this research indicates three political characters of the prophets. First, as mediator between Yahweh and Israel, prophets did not only work in religious-cultic affair, but also in a socio-political affair, especially in the monarchy period of Israel. Secondly, peace and prosperity among the people of God are significant fruits of prophetic works in society. Thirdlly,Â as the chosen people of God, Isaiah and Jeremiah had led leaders of Judah to embody and actualize justice and peace as well as prosperity.Â Prophets are important part of the people of God as well as political beings.